2019
DOI: 10.1073/pnas.1915562116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of chaperone interactions on MHC-I for folding and antigen repertoire selection

Abstract: The interplay between a highly polymorphic set of MHC-I alleles and molecular chaperones shapes the repertoire of peptide antigens displayed on the cell surface for T cell surveillance. Here, we demonstrate that the molecular chaperone TAP-binding protein related (TAPBPR) associates with a broad range of partially folded MHC-I species inside the cell. Bimolecular fluorescence complementation and deep mutational scanning reveal that TAPBPR recognition is polarized toward the α2domain of the peptide-binding groo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 66 publications
6
36
0
Order By: Relevance
“…In our own prior studies, deep mutagenesis of human membrane proteins was used to understand how sequence relates to folding based on surface localization, as misfolded sequences were retained intracellularly due to quality control machinery [50,51,79]. However, PDGFRα is an exception, and nearly every missense mutation still reaches the plasma membrane, including those that are incompatible with the native folded structure (for example, mutations that disrupt disulfides, create cavities, impose steric clashes, or introduce buried charges).…”
Section: Discussionmentioning
confidence: 99%
“…In our own prior studies, deep mutagenesis of human membrane proteins was used to understand how sequence relates to folding based on surface localization, as misfolded sequences were retained intracellularly due to quality control machinery [50,51,79]. However, PDGFRα is an exception, and nearly every missense mutation still reaches the plasma membrane, including those that are incompatible with the native folded structure (for example, mutations that disrupt disulfides, create cavities, impose steric clashes, or introduce buried charges).…”
Section: Discussionmentioning
confidence: 99%
“…S10A-H), demonstrating that the TAPBPR G24-R36 loop employs a similar mechanism to promote peptide capture irrespective of peptide length. DISCUSSION Recent structural studies have revealed that chaperone-mediated peptide exchange/editing is achieved through (i) stabilization of the peptide-deficient MHC-I in a peptide-receptive conformation, (ii) ejection of suboptimal peptides by inducing an ~3 Å widening of the MHC-I groove, and (iii) regulation of a dynamic switch located in the MHC-I groove (Jiang et al, 2017;McShan et al, 2018McShan et al, , 2019Thomas and Tampé, 2017). Despite these important findings, the mechanistic details of how chaperones influence the repertoire of MHC-I presented antigens remains incompletely characterized, while a significant difference between published X-ray structures challenge the proposed role of the TAPBPR G24-R36 loop as a direct peptide competitor.…”
Section: The Tapbpr Loop Promotes Formation Of a Transiently Bound Pementioning
confidence: 99%
“…Solution NMR experiments provide clear evidence for a lack of a direct interaction between the TAPBPR G24-R36 loop and the HLA-A*02:01 groove (Fig. 4C), however in vitro binding data were acquired using the human HLA-A*02:01 heavy chain and it remains unclear how differences in amino acid polymorphisms within other MHC-I, such as the mouse H2 groove, influence behavior of the TAPBPR G24-R36 loop (McShan et al, 2019;Morozov et al, 2016). While we did not find differences in the formation of empty H2-D d /TAPBPR or HLA-A*02:01/TAPBPR complexes in vitro by SEC ( Fig.…”
Section: The Tapbpr Loop Promotes Formation Of a Transiently Bound Pementioning
confidence: 99%
See 2 more Smart Citations